Las desventuras de la potencia (otras consideraciones inactuales) - Pardo, José Luis (Logos. Anales del Seminario de Metafísica, 2002)
The will to escape from the so called Metaphysics of Presence has become a topic in contemporary philosophy. However, this topic is often related to the primacy, in ancient thought, of the actual being, and the correlative evaluation of the potential as an imperfect way of existence. In this text we first analyze the traditional interpretation of the foundations of this primacy in Aristotle’s philosophy, that exhibits a theological form. According to this we explore, in the second part of the article, how the efforts of modern thinkers to build an ontological discourse free from this primacy have produced, in some cases, a kind of Umkehrung resulting in a Metaphysics of Absence that preserves the theological form and results in a primacy of the potential, that is specifically consistent with the Imperium of the Virtual, very illustrative of nowadays conceptions of time, language, power and being. Finally, we essay to offer another interpretation of the primacy of the actual in Aristotle’s Ethics and Metaphysics, which could identify a political philosophy capable to avoid the infertile alternative Presence/Absence in ontology.